Transversal Competences and Employability of University Students: Converging towards Service-Learning - Miguel A. Santos Rego; Daniel Sáez-Gambín; José Luis González-Geraldo; David García-Romero (MDPI AG, 2022)
We are living in times of great transformations within the field of education and the labor market. These changes are connected and have to do with an expanded knowledge society, whose implications reach the levels of employability in times of uncertainty. Within this framework, the main purpose of our study is to perform a theoretical analysis and an empirical approach to the influence that transversal competences (soft skills) may have on the degree of employability of university students. We have identified some of those competences and we have tested them with a sample of 83 employers and 1249 students using a Likert scale. Our results show the interest of employers in the mastery of transversal competences and inequalities in terms of students' perception thereof. We did not find any significant differences between students starting their degree and those who were about to complete it. However, we did find differences between the students who participated in experiential activities and those who did not, in favor of the former. Due to the importance of experiential learning in our results, we dedicate our discussion to theoretically exploring whether the pedagogical approach of Service-Learning (SL) might contribute to a better connection between transversal competences and employability.